(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article presents the development of a mathematical model for ensuring energy-efficient operation by considering the electromagnetic and mechanical dynamics of an asynchronous motor. The model is simulated using the Simulink package of the MATLAB software, allowing analysis of the motor’s static and dynamic states as well as optimization through control systems. The general dynamics of the asynchronous motor are expressed using equations based on a genetic algorithm, enabling precise modeling of its operational parameters. Control over parameters such as flux, torque, and angular velocity ensures optimal energy consumption. Artificial neural networks are incorporated to manage load and speed, contributing to increased energy efficiency.